Implementasi Kebijakan Pencegahan Penyebaran Corona Virus Disease (Covid-19) di Universitas Jember - Suharsono, Agus; Sari, Vianney Dwi Puspita; Boedijono, Boedijono (Electronical Journal of Social and Political Sciences (E-SOSPOL), 2022)
Corona Virus Disease (Covid 19) is a virus is spreads to almost all countries, including Indonesia. The spread of Covid-19 has had an impact on various fields, one of which is education. One of the government's efforts to overcome this impact is to implement policies to prevent the spread of Covid-19 in universities. In accordance with this policy, the Chancellor of the University of Jember issued the rector's circular letter number 4687/UN25/LL/2020 regarding the prevention of the spread of Covid-19. The purpose of this study is to describe the policy of preventing the spread of Corona Virus Disease (Covid-19) at the University of Jember. This type of research is descriptive qualitative research with the type of data consisting of primary data and secondary data obtained by interviews, observation and documentation. The results of this study indicate that the University of Jember has implemented policies to prevent the spread of Corona Virus Disease (Covid-19) well in terms of communication, resources, disposition and organizational structure. So that students can still get the right to carry out learning and still comply with health protocols